Exploring the Impact of Higher Education on Ethical Values and Professional Integrity among University Students in Pakistan: A Qualitative Study - Shahzadi, Shazia; Juhary, Ali; Rajpoot, Tausif Ahmad; Mashhood, Asher Ahmad (2024)
This article explored university students' perceptions regarding the university's role in fostering an ethical culture. The study adopted a qualitative, exploratory approach, utilizing a semi-structured interview tool developed from a literature review. Interviews were conducted with 15 students from various administrative-related disciplines. Findings indicated that students believe the university plays a significant role in promoting ethical culture and suggested several strategies to enhance this effort. The study concludes that universities, particularly those offering administrative degree programs, should extend their focus beyond merely developing technical and hard skills. Instead, they should embrace their essential role in encouraging reflection on social issues and instilling a sense of responsibility among future business leaders to create value in society.